Family entrepreneurship as a factor of social development - Abugaliyeva, F.; Zhaskairat, M. (Bulletin of the Karaganda University “Law Series”, 2024)
The main purpose of the article is to determine the role that family entrepreneurship plays in the development of the state, forming it as a social factor in the life of society. In the course of the research work, in order to form the concept of “family entrepreneurship”, the advantages of family business in the social and economic sphere and the disadvantages found in practice were identified. The research used historical-legal, comparative-legal, analytical and descriptive research methods. The article discusses topical issues of family entrepreneurship as a social phenomenon and a factor in social development. This paper discusses in detail the strategic and tactical advantages of family entrepreneurship in the process of developing the country's economy, its legal significance. In the course of the study of the topic, the features of family entrepreneurship as a social institution and the importance of strengthening the position of the family in the economy, family relations, family continuity arising from mutual property interaction of family members were revealed. On the topic of the study, the reasons, conditions and stages of the formation of a new legal school are also considered, which leads to the emergence of a legal institution within the framework of modern entrepreneurship. As a result of the study, it was concluded that, given the importance of legislating the institution of “family entrepreneurship”, family business entities, along with strengthening family ties, make a significant contribution to the development of the social and economic spheres of the state, creating a special collective culture based on the values and cultural heritage of the family.